KULIAH KERJA NYATA PMD UNIVERSITAS MATARAM: PENINGKATAN KINERJA EKONOMI DESA MELALUI PENGELOHAN KOPI ALPUKAT KHAS AIK BUKAQ - Saptono waspodo; Wulandari, Dwi Januar; Arrasyid, M. Dzaki; Fidya, Karina Alma; Ramdani, Elsa Destia; Suryani, Erni; Agustina; Islami, Nur Laily; Kurnia, M. Ramdaniq; Aizar, M. Fatihul; kurniawan, Wawan; Agustina, Agustina (Jurnal Wicara, 2025)
Aik Bukaq Village, located in Batukliang Utara District, Central Lombok Regency, has abundant natural potential, especially in the agricultural sector, with superior products in the form of avocado and coffee. However, this potential has not been optimally managed to attract the attention of the outside community. Therefore, this study aims to develop avocado coffee as a superior local product of Aik Bukaq Village which can become a characteristic of the village. Through observation, training, and promotion methods, this activity aims to improve community skills in processing avocado coffee and introduce this product through online and offline marketing (Fitriani & Mulyadi, 2021). The results of the activity show that the development of avocado coffee can improve the local economy and attract tourists (Dewi & Saputra, 2023). This product is also in line with global sustainability trends, reduces waste, and has the potential to become a culinary symbol that supports village tourism (Gunawan & Wibowo, 2020). Thus, the development of avocado coffee in Aik Bukaq Village has the potential to have a positive impact on improving the welfare of the local community and introducing the village as a tourist destination rich in natural and cultural potential.